Moma Titanium Minerals Mine, Mozambique - Mining Technology | Mining News and Views Updated Daily - Mining Technology (Mining-technology, 2021)
Moma, one of the world’s biggest titanium mineral deposits, is located 160km from the city of Nampula in Mozambique, Africa. It is owned and operated by Kenmare Resources. The mine contains the titanium minerals ilmenite, rutile and zircon, which are used as feedstock to produce titanium dioxide pigment. It started production of heavy mineral concentrate (HMC) containing these three minerals in April 2007. It produced 1,201,100t of HMC and shipped approximately 853,100t of finished products in 2020. Kenmare carried out an expansion at the mine ten years ago to fulfil the growing demand for titanium dioxide feedstock in the market. The expansion was aimed to increase the design capacity of the mine by 50% while increasing the mine’s reserve estimate and annual production of HMC. Construction work on the expansion began in December 2010 and the works were completed in December 2013. The expanded mine has a mine life of more than 100 years. The first shipment of concentrated mineral sands was dispatched from Mama in Q2 2019, following the commissioning of the product stream in Q4 2018. The Moma mine had more than 1,420 employees at the end of 2019.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Mozambique: Military maritime cooperation agreement with France under discussion - Lusa (Club of Mozambique, 2020)
Mozambique and France are discussing a military maritime cooperation agreement, a diplomatic source in the European country told Lusa in the context of possible support in the fight against terrorism in Cabo Delgado. "No operational military support has been provided to Cabo Delgado by the French
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; GP - Cabo Delgado; L - english / inglês; conflict / conflito

Implement - Outcome Harvesting|Civicus - CIVICUS (CIVICUS, 2019)
Outcome Harvesting is a M&E methodology used to identify, describe, verify and analyses the changes brought about by a campaign, support or advocacy initiative (see Better Evaluation or Winter School 2019 presentation by Outcome Mapping Learning Community). In Outcome Harvesting, one collects evidence of change (‘outcomes’ – e.g. changed policy, amended or stopped legislation processes, a new coalition formed, shifted voting behaviour) and then works backwards to assess contribution to that change. Please note that the change can also be a negative change, and/or the change cannot be linked to one’s own contributions but rather to those of other actors. It may be referred to as Outcome Mapping methodology. However, in Outcome Harvesting, there are also other methodologies used during the harvest process. Outcome harvesting can be used for ongoing monitoring throughout a project or programme, in order to produce real-time information on change. It can also be used with evaluation or impact assessments during projects or programmes, at the end of a project, or some time after they have been completed. Outcome Harvesting involves participation with different stakeholders. According to Wilson-Grau (2015) participation is described by the methodology’s main developer as necessary for a successful outcome harvesting process and product. Moreover, it is considered most useful under three conditions (see Ricardo Wilson-Grau and Heather Britt 2012): Focus on outcomes rather than activities: It is not designed to assess whether activities were carried out according to plan, rather than assessing what has changed and why. Complex programming contexts: Outcome Harvesting is suitable for complex programming context where the relationship between the cause and the effects is not fully understood. Examples of complex situations could include in areas such as advocacy, mobilization, capacity development, empowerment or network development. Monitoring and evaluation: Outcome Harvesting can also be used when the purpose as an M&E exercise is to learn about the change and understanding why those changes occurred.
Keywords: *tagged; L - english / inglês; M - evaluation / avaliação; M - methodology / metodologia

Strong but not Broadly Shared Growth. Mozambique Poverty Assessment - World Bank (World Bank, 2018)
Mozambique has recorded strong growth, but many low-income households are missing out on the benefits and policy options to make rowth more inclusive in Mozambique
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; poverty / pobreza

Malonda – The Private Sector Support related to Agriculture in Niassa - Carlsson, Lars (SIDA - The Swedish International Development Cooperation Agency, 2003)
Information on the Swedish support to the private sector related to agriculture in Niassa, Mozambique 2003.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; agriculture / agricultura; poverty / pobreza; private sector / setor privado

Subnational HDI - Global Data Lab - Iñaki Permanyer; Jeroen Smits (Global Data Lab - Nijmegen Center for Economics (NiCE), Institute for Management Research, Radboud University)
Subnational Human Development Index - Mozambique
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia

Mozambique HDI Data - UNDP
Access and explore human development data for 191 countries and territories worldwide. Select Mozambique.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia